Sources of Japanese tradition (Columbia University Press, 2001)
For almost fifty years, Sources of Japanese Tradition has been the single most valuable collection of English-language readings on Japan. rivalled in its wide selection of source materials on history, society, politics, education, philosophy, and religion, the two-volume textbook is a crucial resource for students, scholars, and readers seeking an introduction to Japanese civilization.